2019
DOI: 10.1186/s13256-019-2217-2
|View full text |Cite
|
Sign up to set email alerts
|

Papillary squamotransitional cell carcinoma of the uterine cervix: a case report and review of the literature

Abstract: BackgroundPapillary squamotransitional cell carcinoma of the uterine cervix is a rare neoplasm, a subtype of transitional cervical carcinoma that appears to be a variation of squamous cervical carcinoma. It has a disposition toward metastasis at an advanced stage and local recurrence. Owing to the difficulty of illustrating the invasion histologically, misdiagnosis is likely to affect the patient’s prognosis.Case presentationWe present a case report of an 81-year-old Caucasian patient with squamotransitional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
(26 reference statements)
2
16
0
Order By: Relevance
“…Very importantly, gynecological malignancies, mainly cervical and endometrial ones, have also been demonstrated to be related to chronic inflammation, be it mediated by infectious or non-infectious conditions [17,69,70,123]. This highlights the long-term importance of proper diagnosis and management of chronic inflammation.…”
Section: The Concept Of Impaired Inflammatory State Of the Endometriummentioning
confidence: 99%
“…Very importantly, gynecological malignancies, mainly cervical and endometrial ones, have also been demonstrated to be related to chronic inflammation, be it mediated by infectious or non-infectious conditions [17,69,70,123]. This highlights the long-term importance of proper diagnosis and management of chronic inflammation.…”
Section: The Concept Of Impaired Inflammatory State Of the Endometriummentioning
confidence: 99%
“…10,11 It shows aggressive biological behavior and needs close and extended follow up after definitive treatment as it tends to recur locally and can have late metastasis. [12][13][14][15] We herein present a study of detailed histomorphology along with immunohistochemistry (IHC) correlation of 18 cases of PSTCC diagnosed in our institution.…”
Section: Resultsmentioning
confidence: 99%
“…5,9 They were poorly characterized in the literature and it remained unclear for a long time whether these tumors represented a different group of tumors or were within a spectrum of clinically homogenous and morphologically similar entities. 15,17 Marsh, in the year 1952 initially identified these lesions when 3 out of 31 papillary tumors of the cervix turned out to be malignant. Later in 1958, Kazal observed that 2 out of 20 cases reported as squamous cell papillomas of the cervix showed transformation to SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Nafussi and Al -Yusif, in their study, concluded that papillary SCC has a propensity for late metastasis and local recurrence even though histologically it could be misinterpreted as CIN3 with a papillary configuration or as a squamous papilloma [3] . In the literature, the clinical behavior of PSTCC is characterized as almost the same as that of SCC, except for the tendency of PSTCC towards the metastasis and local recurrence [2] . Cervical transitional (SCC) cells have different staining patterns (CK7+/CK20-).…”
Section: Discussionmentioning
confidence: 99%
“…PSTCC can be described as an "in situ" tumour with or without an invasive part but usually with both components existing. Furthermore, it is difficult to distinguish PSTCC from other papillary lesions of the cervix because of its papillary exophytic nature [2] . Hence it becomes necessary to separately identify from the commoner and benign varieties of the cervical papillary lesions like condyloma accuminata and squamous papillomas because of potentially aggressive biological course.…”
Section: Introductionmentioning
confidence: 99%